NutriCare: Aplikasi Pemantau Gizi Ibu Hamil untuk Menghindari Stunting dengan Memenuhi Kebutuhan Kalori dan Zat Besi - Maharani, Tarisyah Puan; Budhisantoso, Nugroho (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Stunting in children under five, due to chronic malnutrition since in the womb, has an impact on children’s health and cognitive development as well as the potential for long-term economic losses. In Indonesia, the prevalence of stunting will reach 21.6% in 2022. Iron and calorie deficiency in pregnant women is the main factor causing stunting, with 48.6% of pregnant women experiencing anemia. Many pregnant women lack easily accessible nutritional information. The Hilda Alnaira Clinic in Koja, North Jakarta, faces challenges in providing manual nutritional recommendations that are inefficient and lack personalization. This research aims to develop the "NutriCare" mobile application to help pregnant women monitor calorie and iron intake. This Android-based application was developed using a prototypemethod, easy-to-use interface, relevant features, tested using the black box method, and optimized before full implementation. This application helps increase pregnant women’s understanding of nutrition and supports maternal health and fetal development in efforts to prevent stunting.